On the fortunes of stock exchanges and their reversals: evidence from foreign listings - Nuno Fernandes; Mariassunta Giannetti (European Central Bank (ECB), 2013)
Using a sample that provides unprecedented detail on foreign listings, new listings, and delistings for 29 exchanges in 24 countries starting from the early 1980s, we document a growing tendency of listings to concentrate in the U.S. and the U.K., and large changes in all exchanges' ability to attract foreign companies. We highlight the following determinants of these patterns. First, during the sample period, investor protection improved in many countries. As investor protection improves in the country of origin, firms become less likely to list in countries with weak investor protection, but more likely to list in countries with strong investor protection, especially in the U.K. and the U.S. Second, we show that foreign listings are related to the exchange's market valuation in the same way that domestic equity issues are and that firms that are more difficult to evaluate are more inclined to list in foreign exchanges with high valuations.
Keywords: G15; G38; M41; M45; F40; 330; Cross-listings; investor protection; market timing; SOX